Local Government Responsibility in Ensuring the Functional Feasibility of Provincial Roads: An Administrative Law and Siyasah Dusturiyah Perspective - Misdin Arifin HM; Salwa Husni Aprilia Pasaribu; Putri Nayla Khairuna Lubis; Rizky Ananda Marpaung; Khoiril Muhammad Ufara Dzikri Nasution (ISNU Nine-Star Multidisciplinary Journal, 2026)
Roadworthiness of provincial roads is a fundamental aspect in ensuring traffic safety and protecting the public interest. Roads that do not meet roadworthiness standards have the potential to cause accidents, material losses, and reflect weak accountability on the part of government authorities. This study aims to analyze the accountability of local governments in fulfilling the roadworthiness requirements of provincial roads from the perspectives of administrative law and siyasah dusturiyah. This research employs a normative legal research method with juridical and conceptual approaches. The research stages involve examining statutory regulations related to road administration, analyzing doctrines of administrative law, and reviewing the thoughts of classical and contemporary Islamic scholars within the framework of maqāṣid al-sharī‘ah. The analysis is conducted qualitatively by assessing the consistency between legal norms and the actual practices of road administration, as reflected in previous studies. The findings indicate that there remains a gap between the normative provisions governing roadworthiness and their implementation at the local government level. From the perspective of administrative law, this condition reflects the weak application of the principles of legality and accountability in public service delivery. Meanwhile, from the perspective of siyasah dusturiyah, negligence in fulfilling roadworthiness requirements constitutes a breach of leadership trust (amanah) and contradicts the principles of protecting life (ḥifẓ al-nafs) and property (ḥifẓ al-māl). This study emphasizes that ensuring roadworthiness is not merely an administrative obligation, but also an ethical and shar‘i duty in realizing public welfare.